Wpływ kontaktu z psem na organizm człowieka - przegląd literatury (dostępny po zalogowaniu tylko dla osób z dysfunkcją wzroku) - Nawrocka-Rohnka, Joanna (Poznań: Wydawnictwo Naukowe Uniwersytetu Medycznego im. Karola Marcinkowskiego)
This article summarizes the latest research findings on the impact of contact with dogs on the cardiovascular, immunological, hormonal system, physical activity and mental health, as well as the functioning of elderly people and children. It may be generally concluded that the main factor guaranteeing the dog?s positive impact on man is human`s positive attitude towards the dog.
Keywords: pies; choroby sercowo-naczyniowe; sekrecja hormonów; aktywność fizyczna; dog; cardio-vascular disease; hormones secretion; physical activity